Study of antimicrobial susceptibility of clinically significant microorganisms isolated from selected areas of Dhaka, Bangladesh (Bangladesh Journal of Medical Science, 2013)
Objective: Pathogenic resistance against antibiotics is substantially mounting in the developing countries including Bangladesh. Present study thus attempted to obtain the baseline information on such resistance among the community people coming to the local dispensaries around the city of Dhaka for treatment. Materials and Methods: A total of 2,700 clinical specimens were examined for the presence of Gram positive and Gram negative pathogens. Antibiotic susceptibility tests of the isolates were carried out. Extended spectrum b- lactamase (ESBL) activity, and the presence of methicillin resistant Staphylococcus aureus (MRSA) and S. epidermidis (MRSE) were also detected. Results: Escherichia coli were most prevalent (45.5%) among 1044 pathogenic bacteria isolated from 2,700 samples. E. coli predominated urine, pus, wound swab, blood, high vaginal swab (HVS) and sputum specimens, and exhibited the highest frequency of ESBL activity (35%). Prevalence of Klebsiella spp. and S. aureus among the clinical specimens were 11.5% and 9.86%, respectively. Most of the Gram negative bacilli were found resistant against ciprofloxacin (5 mg), tetracycline (30 mg) and cotrimoxazole (25 mg). Majority of Pseudomonas spp. were found resistant against most of the commonly used antibiotics. Interestingly, around half of the S. aureus isolates were observed to be methicillin resistant, but not vancomycin resistant. Conclusion: Overall, such a revelation of increased antibiotic resistance demands for restrictive and appropriate antibiotic usage in accordance with the updated antibiotic prescribing policy in Bangladesh. DOI: http://dx.doi.org/10.3329/bjms.v12i1.13351 Bangladesh Journal of Medical Science Vol. 12 No. 01 January13 pp.34-42